Invisible NIR Spectral Imaging and Laser‐Induced Thermal Imaging of Na(Nd/Y)F4@glass with Opposite Effect for Optical Security. Issue 8 (18th May 2022) - Wang, Shaoxiong; Zhu, Jiwen; He, Youwu; Li, Zhifang; Lin, Jidong; Liao, Shengxiang; Huang, Feng; Huang, Ping; Zheng, Yuanhui; Li, Xiaoyan; Chen, Daqin
Abstract: Currently, advanced optical security techniques are imminent in response to the increasingly rampant counterfeit and pirated goods on a global scale. Herein, hexagonal Na(Nd x Y1− x )F4 ( x = 0–1) solid‐solution nanocrystals (NCs) embedded glasses are successfully fabricated via in situ glass crystallization. Benefited from the protection of inorganic glass, Na(Nd x Y1− x )F4 NCs exhibit superior long‐term stability and can endure high‐power 808 nm laser irradiation. Importantly, opposite variations between near‐infrared (NIR) luminescence and laser‐induced temperature can be detected for the nanocomposites, which are sensitive to Nd 3+ doping concentration. As a proof‐of‐concept experiment, Nd 3+ concentration dependent anti‐counterfeiting patterns with high‐concealment and high‐precision are designed and show bright emission and dimmish thermal images in Nd 3+ ‐tenuous composites under the irradiation of 808 nm laser, while opposite displays can be achieved in Nd 3+ ‐enriched one. This kind of information encryption triggered by a commercial single light source to achieve dual opposing displays in one material can effectively improve security in anti‐counterfeiting. Abstract : Dual‐mode imaging from NIR luminescence and photothermal effect in the Na(Nd/Y)F4 @glass nanocomposite triggered by a commercial 808 nm laser is reported. Both spectral imaging and thermal imaging are invisible by naked eyes and are inversely sensitive to Nd 3+ concentration, which enable them to find practical application in high‐level optical security.